Targeting the Innate Immune System as Immunotherapy for Acute Myeloid Leukemia - Curran, Emily; Corrales, Leticia; Kline, Justin (Frontiers in Oncology, 2015)
Because of its disseminated nature and lack of tumor-draining lymph nodes, acute myeloid leukemia (AML) likely employs unique immune evasion strategies as compared to solid malignancies. Targeting these unique mechanisms may result in improved immunotherapeutic approaches. Emerging data suggests that a specific dendritic cell (DC) subset, CD8α DCs, may be responsible for mediating tolerance in AML and thus targeting the innate immune system may be of benefit in this disease. Promising immune targets include the Toll-like receptors (TLRs), calreticulin/CD47, the stimulator of interferon genes (STING) pathway and signal transducer and activator of transcription 3 (STAT3). However, it is becoming clear that compensatory mechanisms may limit the efficacy of these agents alone and thus rationale combinations of immunotherapies are warranted. This review discusses the potential immune evasion strategies in AML, as well as discussion of the promising innate immune targets, both alone and in combination, for this disease.